State of the Art dari Pembelajaran Matematika Berdiferensiasi: Tinjauan Literatur Sistematis - Anggraeni, Wulan; Suryana, Andri; Nurhayati, Nurhayati; Suyahya, Indra (Neolectura, 2025)
Literature review using Systematic Literature Review (SLR) on differentiated mathematics learning (MDI) related to content, process, and product differentiation is still rare. Therefore, the purpose of this study is to conduct a literature search on MDI related to content, process, and product differentiation. The stages of SLR are planning, article search, analysis, and interpretation of results. The digital libraries used are Scopus and Science Direct. The selection process uses the Preferred Reporting Items for Systematics Reviews (PRISMA) method. Based on the selection process, two main articles were obtained. The article analysis process was carried out in two stages, namely bibliometric analysis to determine the relationship between words used in previous studies, and article analysis by answering research questions compiled in the planning stage so as to obtain the state of the art. The results of the article review analysis obtained that there is no continuous teacher professional development on content, process and product differentiation based on multiple intelligences, learning styles, learning readiness levels, learning motivation, self-concept, critical and creative thinking abilities of students, no development of mathematics instruction for problem solving, connection, communication, reasoning, critical thinking, or mathematical creative thinking, no assessment of students' affective responses to MDI, and no clustering of students using the K-Means and K-Medoids methods. The results of this study are expected to provide knowledge and further research development related to MDI.